Analisis Problematika Guru dalam Menghadapi Anak Berkebutuhan Khusus (ABK) terhadap Implementasi Program Pendidikan Inklusi - Erni Kurniawati; Andika Rahman; Dewi Kurniawati; Opi Andriani (Institut Nalanda, 2024)
The aim of this research is to determine the problems of teachers in dealing with children with special needs regarding the implementation of inclusive education. The method used in this research is a literature review study. Literature study is a research design used to collect data sources related to a topic found in the field. Data collection for literature studies was carried out using the Google Scholar search tool. The appropriate and required screening results contained 5 National Journal articles based on the articles found and analyzed. The results of this research are that teachers have problems dealing with children with special needs, namely teachers have difficulty in designing lesson plans, teachers have difficulty developing the learning methods used, children with special needs are difficult to manage and infrastructure needs to be considered in order to increase the convenience for teachers in dealing with children with special needs.